The Role of Social Support in Enhancing Motivation and Psychological Well-being of Students: Perspectives from Education in the Digital Era - Marjuki; Hanif, Muh.; Siminto (Indo-MathEdu Intellectuals Journal, 2024)
The digital era has fundamentally transformed the paradigm of education. Nowadays, students not only interact with learning materials but also with various digital platforms that offer access to unlimited resources and information. This research aims to analyze the role of social support in enhancing motivation and psychological well-being of students from the perspective of Education in the digital era. The research method employed in this study is a literature review with a qualitative approach and descriptive analysis. Data for this study were gathered from Google Scholar spanning from 2013 to 2024 through a focus on the keywords social aspects, motivation, psychological well-being of students, education, and the digital era. The results of the study indicate that social support is a crucial factor influencing the motivation and psychological well-being of students in the context of education in the digital era. Despite the continuous evolution of technology, genuine human relationships and emotional support remain key pillars in shaping positive learning experiences. Social support emanates from various sources, including peers, family, faculty, and academic communities. The expansion of technology usage enables the preservation of social connections, although it is important to note that the quality of interactions in the virtual world may not always be equivalent to face-to-face interactions.